Integrating Modern Technologies and Intelligence Systems for Infectious Disease Preparedness: A Strategic Review - Pasma, Satriani Aga (Security Intelligence Terrorism Journal (SITJ), 2025)
Infectious disease outbreaks remain a persistent threat to global health, social stability, and national security. In recent years, the intersection of modern technology and public health has introduced transformative tools to enhance outbreak anticipation, surveillance, and response. This review aims to explore how technological innovations particularly artificial intelligence (AI), the Internet of Things (IoT), and digital health platforms can be strategically leveraged to strengthen national preparedness against emerging infectious diseases, with an emphasis on the intelligence sector’s role. Utilizing a systematic literature review approach, the study draws insights from scholarly articles, policy documents, and case studies published over the past ten years. Findings show that integrating technology into surveillance and early warning systems significantly improves detection and mitigation capabilities. However, challenges persist in data privacy, interoperability, and resource disparities, especially in developing countries. This paper highlights the importance of multisectoral collaboration, investment in digital infrastructure, and policy innovation to ensure that technological advancement translates into effective public health outcomes.